Analysis of Energy and Exergoeconomic on Water Cleaning and Injection Facilities in the CPP Block, Indonesia - Hamdani Wahab; Awaludin Martin (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
One of the problems in the upstream oil and gas industry is that large quantities of produced water must go through a water cleaning and injection process in accordance with the Regulation of the State Minister of the Environment Number 19 of 2010 of the Republic of Indonesia concerning the quality standards of wastewater for oil and gas and geothermal activities. A total of 224,257.1 barrels of water per day which is produced water in the CPP Block must go through a water management process which requires a large energy consumption of 269.47 MW/month. One effort to reduce the use of electrical energy is to conduct energy and exergy analysis to determine the point of greatest energy use as a result of exergy destruction and convert it into economic costs as operating cost losses. From the research, it is known that the largest electrical energy consumption is at the injection pump 235.47 MW/month with exergy 67.72 KW, the largest exergy destruction is 31.04 KW at the charge filter pump with an efficiency of 54%. Energy and exergy analysis is used to identify changes in energy quality in a system.